Developing PBL-based worksheets on sequences and series to enhance mathematical connection skills of senior high school students - Puspita, Nurhaliza Citra; Heleni, Susda; Suanto, Elfis (Jurnal Gantang, 2025)
This study was driven by students’ low mathematical connection ability in learning Sequences and Series, a skill essential for understanding relationships among mathematical concepts. The purpose of this research was to develop a Problem-Based Learning (PBL)-based student worksheet designed to improve students’ mathematical connection ability and to examine its validity and practicality. A development research approach was applied using the 4-D model—Define, Design, Develop, and Disseminate. The participants were tenth-grade students selected through purposive sampling. Data were collected using validation instruments, practicality questionnaires, interviews, and classroom observations. The validation process evaluated face, content, and construct validity. The developed worksheet demonstrated strong validity, with average scores of 89.29% for face validity, 89.29% for content validity, and 86.79% for construct validity. The overall validity score of 88.45% fell into the “very valid” category, indicating the product’s suitability for field implementation. The practicality assessment, focusing on design, clarity of material presentation, and ease of use, produced an average score of 83.27%, classified as “practical.” These findings suggest that the PBL-based worksheet is both valid and practical, offering potential as an effective instructional tool to support students in developing mathematical connection ability, particularly in topics related to Sequences and Series.